MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL SCRAMBLE BERBANTUAN MEDIA BLOCK DIENES MATERI PENJUMLAHAN BILANGAN CACAH DI SEKOLAH DASAR - Rahmawati Gobel; Muhammad Sarlin; Nur Sakinah Aries (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aimed to enhance students' learning outcomes through the Scramble model assisted by Dienes Block media on adding whole numbers in Class I at SDN 16 Tibawa. In the meantime, this research employed a classroom action research design with the subjects of 21 students in Class I. Based on the results from the cycle 1, 13 students, or 62%, achieved the Minimum Completeness Criteria (MMC). These results did not meet the expected success indicators, prompting a continuation of cycle II. In the cycle II, 19 students, or 91%, achieved the MMC. This result met the success indicator set at 75%, representing a 29% improvement. It could be concluded that the Scramble model assisted by Dienes Block media could enhance students' learning outcomes by adding whole numbers in Class I at SDN 16 Tibawa.